Synthesis of New Thienopyridine Derivatives by [3+2]- and [2+2]-Cycloaddition Reactions - Milen, Mátyás; Ábrányi-Balogh, Péter; Dancsó, András; Keglevich, György (Synthesis, 2012)
The reaction of 6,7-dihydrothieno[3,2-c]pyridine derivatives with 1,3-dipoles, such as a nitrile oxides or nitrile imines, gave novel fused heterocycles. The Staudinger reaction of the starting material was also studied. This reaction was stereoselective and exclusively gave racemic cis-cycloadducts in which the thienopyridine core was fused with a β-lactam ring.
Keywords: heterocycles; cycloadditions; nitrile oxides; nitrile imines; Staudinger reactions